PARTICLE SIZE VARIATIONS IN THE GLASS COMPONENT OF GLASS-IONOMER DENTAL CEMENTS - Iqbal, Kefi (Journal of Ayub Medical College Abbottabad, 2012)
Background: Glass polyalkenoate cements (glass ionomer cements) are widely used in restorative dentistry and now a day the material of choice for bone cements. The aim of the study is to examine the variations produced by exposure to acid for dental Glass Ionomer Cement (GIC) glass particles of different composition. It also involves the study of the effect of replacing Ca by Sr in glass ionomer glasses on the particle size distribution. Methods: This study was carried out in a Malvern Mastersizer/E. This uses LASER-diffraction and was in reverse-Fourier mode (0.1-80 µm). Ultrasound was used to break up any agglomerates. Also, some samples were treated as above but instead of particle size analyser, the slurries were centrifuged and the glass washed and dried to constant weight to determine mass loss. Results: The mass loss for LG26Sr in acid washing was comparatively greater whereas LG26 showed less mass loss. When statistically evaluated LG series and AH2 were found to differ significantly p=0.008. There was, however, no significant difference between other combinations of glasses in acid was treatment. The pseudocement formation in all the glasses suffered significant mass loss p=<0.008. Conclusion: By changing the different chemical composition of glass ionomer glasses the mass loss was substantially greater during the cement formation process as compare to acid washing. Keywords: Glass ionomer cement, Components of glass ionomer cement, Restorative material, Luting material.